Формування маркетингової системи збуту продукції аграрного підприємства - Багорка, Марія Олександрівна; Bahorka, Mariia; Квасова, Людмила Сергіївна; Kvasova, Liudmila; Кравець, Ольга Василівна; Kravets, Olga (Класичний приватний університет, 2023)
В статті проведено дослідження сутності, функцій та складових маркетингової системи, надано її наукове обґрунтування, представлені заходи, які забезпечують збут продукції аграрного підприємства. Виділено проблеми інфраструктури та доступу до ринку, розглянуто обмеження виробництва основних видів сільськогосподарської продукції, оскільки вони мають важливі наслідки для розвитку інфраструктури та ринку, функціональні та інституціональні складові маркетингової системи. Встановлені складові маркетингової системи відповідно до відмінностей аграрної продукції: швидке псування, сезонне виробництво, шляхи сполучення, умови зберігання. Автори дійшли до висновку, що саме канали розподілу виступають ключовим модулем функціонування системи просування продукції підприємств аграрного бізнесу, окремо виділено оптовий канал реалізації. The article examines the essence, functions and components of the marketing system, provides its scientific justification, presents measures that ensure the marketing of agricultural enterprise products. A marketing promotion system is a process of facilitating stakeholders that include suppliers, farmers, market agents, processors, retailers and consumers. It was established that the purpose of an agro-industrial enterprise should correspond to the implementation of a set of marketing functions, the essence of which is as follows: firstly, market orientation, which involves the study of its objects and subjects, i.e. consumers, competitors, information about market conditions and products; secondly, influence on the market through its study and analysis, adaptation to market conditions; thirdly, the organization of the sales system of competitive products, the collection and processing of information; fourthly, orientation towards achieving long-term commercial success, which involves the subordination of short-term interests to the goals of long-term, stable market advantages. Distinctive features of the marketing system of agricultural production are determined by the specifics of markets in the agribusiness system, features of supply and demand, as well as prices for agricultural products. It is the marketing system that allows you to partially or fully solve the problems of promoting agricultural products, to form appropriate strategies that will contribute to increasing the efficiency of the enterprise and give a positive result. Step-by-step formation of the marketing system involves: carrying out analytical diagnostics of the agricultural enterprise and strategic forecasting (forecasting) of its development; development of a marketing complex; ensuring effective organization and effective marketing management. The components of the marketing system are established according to the differences in agricultural products: perish ability, seasonal production, communication routes, storage conditions. The authors came to the conclusion that it is the distribution channels that are the key module of the functioning of the product promotion system of agrarian business enterprises, and the wholesale sales channel is separately highlighted.
Formation of a marketing system for the sale of products of an agricultural enterprise
Keywords: маркетингова система; marketing system; збут продукції; marketing product; канали розподілу; distribution channels; комунікативні заходи; communication activities; аграрна продукція; agricultural products; споживачі; consumers